Sejarah Dan Dinamika Pemikiran Dalam Muhammadiyah - Mutmainnah, Nurul; ., Nursyamsani; Amin, Muh. (CV. ITTC INDONESIA, 2026)
Muhammadiyah is one of the largest Islamic organizations in Indonesia, playing a significant historical and intellectual role. This study aims to describe the historical background of Muhammadiyah's birth, analyze the dynamics of religious thought from its early stages to the contemporary era, and explain its contribution to the nation. This study uses a qualitative approach with a descriptive-historical method. The results show that the birth of Muhammadiyah in 1912 was a response to the socio-religious conditions of society and the influence of global Islamic renewal. The dynamics of Muhammadiyah thought evolved from a focus on purification to the formulation of a